PERANCANGAN DESAIN BIOPHILIC PADA PERPUSTAKAAN UMB PEJATEN DI JAKARTA SELATAN - Tjoanda, Frais Charles; Permatasari, Rr Chanrarezky (Anggada : Jurnal Desain dan Seni, 2021)
Libraries can also be interpreted as a collection of information that is scientific, entertainment, and recreational which is an essential human need. Therefore, the modern library has been defined as a place to access information in any format, whether the information is stored in the library building or not. The activities that can support the needs of space users other than reading are in the form of training areas, multimedia areas, and other activities. Of all these things, the activities can run well, but good benefits or impacts are also needed for space users who are not just reading and other activities, but also have a positive impact on the body such as nuances that can affect mental and health which can create more effects. . calm down, reduce stress levels and be more productive. So in this design I want to apply a design concept with a biophilic theme where there are green plants in the room as well as a room sweetener, or decoration, as well as an attractive appearance in the room that shows the elements of nature itself, which can answer the main problem of psychology. and health of space users. Due to the current COVID-19 pandemic, the activities carried out will be adjusted to the applicable health protocols in accordance with the recommendations from the government. The method used in this design is from the concept of data literature, so that it can make a start that has been developed from stage to stage through also the necessary requirements. That way, the Biophilic concept can be applied to a concept that provides a new atmosphere, as well as providing good benefits for space users and providing a different perception for space users to Biophilic designs which have benefits other than the aesthetic appearance of the space design, on interior elements.